FPGA Based High Performance Torque and Flux Estimator - Sutikno, Tole; Jidin, Auzani; Jidin, Aiman Zakwan; Nik Idris, Nik rumzi (Praise Worthy Prize, 2011)
This paper presents a new design of the torque and stator flux estimators for Direct Torque control (DTC) for Field Programmable Gate Array (FPGA) implementation, which permit very fast calciilations. An alternative variable word-size approach in two's complement fixed-point format is used for the implementation, in order to minimike calculation errors and the hardware resource usage. The simulation results of DTC model in Matlab, which performed double precision calculations, are used as references to digital computations executed in FPGA implementation. The Hardware-in-the-loop (HIL) method is used to verify the minimal error between Matlab simulation and the experimental results, and thus the well-functionality of the implemented estimators.